Pengolahan Total Coliform Menggunakan Kombinasi Metode Wetland dan Sinar UV - Tanti Utami Dewi; Ulvi Pri Astuti; Ahmad Erlan Afiuddin; Bhagaskara Cipta Linuwih; Novi Eka Mayangsari (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2022)
Total coliform level contained in the effluent of the shipbuilding industry WWTP in East Java has exceeded the threshold value, respectively 6000-15.400 cfu/100 mL. Threshold value of Domestic Wastewater published by Minister of Environment and Forestry Regulation Number 68 in 2016 mentioned that total coliform allowed to discharge to water column is 3000 CFU/100mL. The number of total coliforms in river can cause health problems in humans and animals so that further processing is needed. In this study, a combination of Wetland and UV light disinfection methods was used to reduce total coliform levels. In the wetland method using a Cattail plants (Typha angustifolia) to reduce the total coliform. This study varied the length of contact time (4, 8, and 12 days) in wetlands and irradiation time (10, 20, and 30 minutes) in UV disinfection in order to obtain the best variation in treating total coliforms found in WWTP effluent. The results showed that all variations of the combination of wetland treatment and UV light were able to remove the total coliform concentration below the quality standard. The best combination variation based on the results of the Two Way Anova Analysis obtained a combination method of 4 days of contact time and 10 minutes of irradiation with a P-value of 0.020.